2000
DOI: 10.1093/ortho/27.1.39
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the Stresses Generated in a Bonded Orthodontic Attachment by Three Different Load Cases Using the Finite Element Method of Stress Analysis

Abstract: The objective of the investigation was to develop a clinically valid three-dimensional computer model of the orthodontic bracket-cement-tooth continuum, and determine the magnitude and distribution of stresses generated by three different load cases. A three-dimensional finite element model of the bracket-cement-tooth system was constructed consisting of 15,324 nodes and 2,971 finite elements. The stresses induced in the bracket-tooth interface by a masticatory load, a peel force and a twisting couple were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 15 publications
4
32
0
5
Order By: Relevance
“…A de-bonding shear force can detach the bracket more easily than the other forces, with the lowest risk of enamel loss. This finding is consistent with the work of Rossouw and Terblanche (1995) and Knox et al (2000), who found that (1) the shear mode was safer for de-bonding brackets than the tensile mode, and (2) torque more often caused damage to the enamel than did shear.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A de-bonding shear force can detach the bracket more easily than the other forces, with the lowest risk of enamel loss. This finding is consistent with the work of Rossouw and Terblanche (1995) and Knox et al (2000), who found that (1) the shear mode was safer for de-bonding brackets than the tensile mode, and (2) torque more often caused damage to the enamel than did shear.…”
Section: Discussionsupporting
confidence: 92%
“…Bracket detachment is usually caused through shear peeling, tensile forces or torque (Wang et al, 1997;Kapur et al, 1999;Rix et al, 2001) by clinicians. Many studies have focused on the stress distribution at an enamel/adhesive/bracket interface in various detached loading modes, but no comprehensive survey of the enamel damage associated with the micro-interlocking mechanism between resin tags has been carried out (Rossouw and Terblanche, 1995;Knox et al, 2000;Valletta et al, 2007;Chen et al, 2008). A reduction in the size of the brackets and their bases has also been proposed to produce a smaller retentive area, which Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, ARI and Ca scores were identical in both methods despite the differences in debonding forces. The explanation to this dichotomy is that cracks probably initiated at the adhesive layer and propagated to either the bracket/adhesive or the adhesive/enamel interfaces (Knox et al, 2000). Since metal brackets bonded with light-cure bonding material were examined in this study, the strength (complete polymerization) of the adhesive material was initially weaker at the bracket/adhesive than at the enamel/adhesive interface, as light-cured Table 2 Correlations between adhesive remnant index (ARI), calcium remnant (Ca) and debonding strength (DS) for each tooth (1 -5) in the two debonding methods.…”
Section: Article In Pressmentioning
confidence: 99%
“…Greater tooth damage may found in twisting disengagement techniques than in shear/peel (Knox et al, 2000). Excessive debonding strength (>11.3 MPa) causes enamel cracks that are less likely to appear when lower forces are applied (7.3 MPa) (Bishara et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Stress distribution in bracket-adhesive-tooth system has been known as a good parameter to estimate and compare the bond strength of different systems [2,3]. Primary studies had used two dimensional finite element models to obtain stress distribution in systems [4,5]. Subsequent studies performed three dimensional analyses that were more accurate, nevertheless most of these efforts led to low quality three dimensional models because they did not consider the reality of tooth structure, its irregularity and asymmetry.…”
Section: Introductionmentioning
confidence: 99%